PENGARUH PENGALAMAN PRAKTIK KERJA LAPANGAN (PKL) DAN LITERASI DIGITAL TERHADAP KESIAPAN KERJA SISWA JURUSAN MANAJEMEN PERKANTORAN SMKN 12 JAKARTA - Nur Hidayat; Darma Rika Swaramarinda; Ferry Setyadi Atmadja (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Increasingly intense competition in the labor market requires vocational high school (SMK) graduates to master not only academic competencies but also practical skills and adaptability to digital technology. However, the gap between graduates' competencies and industry needs remains a challenge, including among Office Management students at SMKN 12 Jakarta, where preliminary research indicated that not all students felt ready to work despite having Field Work Practice (FWP/PKL) experience and digital skills. This study aims to examine and analyze the effect of FWP Experience and Digital Literacy, both partially and simultaneously, on Work Readiness among Office Management students at SMKN 12 Jakarta. This study employed a quantitative approach with a causal associative design. Data were collected through questionnaires from 72 twelfth-grade students who had completed their internships, used a total sampling technique, and analyzed using multiple linear regression via SPSS. The results show that FWP Experience has a positive and significant effect on Work Readiness, whereas Digital Literacy has a negative and significant effect, presumably because the measurement instrument emphasizes passive digital competencies more than problem-solving competencies. Simultaneously, both variables significantly affect Work Readiness, contributing 29.3%, while the remaining 70.7% is explained by other factors outside the model. These findings underscore the importance of strengthening internship programs and reorienting digital literacy learning toward applied competencies to enhance the work readiness of vocational high school students.